The Ability of Short-term Accounting Accruals to Predict Cash Flows of Algerian Companies - Bilal, Kimouche (An-Najah University Journal for Research - B (Humanities), 2020)
هدفت الدراسة إلى استكشاف مدى قدرة المستحقات المحاسبية قصيرة األجل على التنبؤ بالتدفقات النقدية، حيث شملت 14 شركة جزائرية بين 2003 و،2015 ليبلغ عدد المشاهدات الكلية خالل الفترة 117 مشاهدة. وقد تم قياس التدفقات النقدية بصافي التدفقات النقدية التشغيلية، وتم التعبير عن المستحقات المحاسبية قصيرة األجل بـ: التغير في حسابات الزبائن والمدينين، التغير في حسابات الموردين والدائنين، والتغير في المخزونات. وقد أثبتت النتائج ضعف قدرة المستحقات المحاسبية قصيرة األجل على التنبؤ بالتدفقات النقدية للفترة المقبلة، حيث كانت عالقة هذه األخيرة ببنود المستحقات المحاسبية قصيرة األجل غير معنوية، باستثناء عالقتها بالتغير في حسابات الموردين والدائنين This study aims to explore the ability of short-term accounting accruals to predict cash flows. It included 117 observations during 2003 to 2015, which concern 14 Algerian companies. Cash flows have been measured by operating cash flow (OCF). However, short-term accounting accruals have been expressed by change of accounts receivable and debtors, change of accounts payable and creditors, and change of inventories. The results indicated a failure of current short-term accounting accruals to predict cash flows of next period. Except for change of accounts receivable and debtors, the correlations of future operating cash flows with other Short-term accounting accrual items are not significant.
Keywords: Cash flows; Change of accounts payable and creditors; Change of accounts receivable and debtors; Change of inventories; Long-term accounting accruals; Short-term accounting accruals

دور البنوك التجارية في مكافحة عمليات غسيل الأموال - بومدين, نبية (Ibn Khaldun University of Tiaret, 2020)
تعتبر البنوك التجارية من أهم المحطات المالية التي تقوم بعمليات قبول الودائع ودفعها عند الإستحقاق كما تساهم في عملية خلق النقود بكميات كبيرة هذا ما جعلها الأكثر عرضة لجريمة غسيل الأموال والغاية من هذا هو معرفة كيف تكافح هذه البنوك لجريمة خطيرة مثل هذه والتي سادت كل العالم هذا ما أدى إلى دراستنا لهذا الموضوع الذي إعتمدنا فيه على المنهج الوصفي التحليلي و بالتالي عند دراستنا له توصلنا إلى مجموعة من النتائج تتجلى في معرفة الظاهرة بأنها ظاهرة خطيرة سريعة الإنتشار ،عرضة البنوك بهذه الظاهرة كونها تقوم بعدة عمليات ،وجوب على الدولة أن تكافح هذه الجريمة وذلك بوضع قوانين تشريعية تعاقب كل من قام بإرتكاب هذه الظاهرة الخطيرة. Commercial banks are considered one of the most important financial stations that carry out the processes of accepting and paying deposits at maturity and also contribute to the process of creating money in large quantities. This led to our study of this subject, in which we relied on the descriptive and analytical approach, and therefore upon our study of it, we reached a set of results that are evident in the knowledge of the phenomenon that it is a dangerous and rapidly spreading phenomenon. The banks are exposed to this phenomenon as they carry out several operations. Legislative laws punishing anyone who committed this dangerous phenomenon.
Keywords: Banques commerciales; Blanchiment d'argent; Système bancaire; البنوك التجارية; الجهاز المصرف; جريمة غسيل الاموال